2009
DOI: 10.1021/ef9006005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Asphaltenes and Asphaltene Model Compounds by Laser-Induced Acoustic Desorption/Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Laser-induced acoustic desorption (LIAD)/electron ionization (EI) was used to study asphaltene model compounds and asphaltenes derived from North American crude oil in a Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer (MS). Successful desorption by LIAD of all model compounds (including a polyphenylated vanadoyl porphyrin) as intact neutral molecules into the mass spectrometer indicates that this method allows the evaporation of most if not all components of asphaltenes into mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
118
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 56 publications
(92 reference statements)
13
118
0
Order By: Relevance
“…According to Yen-Mullins model, asphaltene molecules are dominated by island architecture with most probable molecular weight of 750 Da, as supported by recent mass spectral analysis. [39][40][41] Approximately six asphaltene molecules form a nanoaggregate via -stacking of their PAH cores. The asphaltene nanoaggregates can further associate to form clusters with aggregation numbers of approximately eight.…”
Section: Asphaltenesmentioning
confidence: 99%
“…According to Yen-Mullins model, asphaltene molecules are dominated by island architecture with most probable molecular weight of 750 Da, as supported by recent mass spectral analysis. [39][40][41] Approximately six asphaltene molecules form a nanoaggregate via -stacking of their PAH cores. The asphaltene nanoaggregates can further associate to form clusters with aggregation numbers of approximately eight.…”
Section: Asphaltenesmentioning
confidence: 99%
“…Asphaltenes have a tendency to degrade and aggregate upon introduction into the gas phase. 28,[37][38][39] Dissolution of asphaltenes for mass spectrometry experiments requires a careful choice of a solvent. 28,40 Ionization bias is another concern because of the highly complex composition of asphaltenes.…”
Section: Introductionmentioning
confidence: 99%
“…37,[42][43]44 A variety of additional desorption/ionization methods have been utilized for asphaltene analysis, such as matrix-assisted laser desorption/ionization, 14 field desorption/field ionization, 45 and laser-induced acoustic desorption/electron ionization. 39 In this work, positive ion mode APCI doped with carbon disulfide (CS 2 ) was used to evaporate and ionize six petroleum asphaltene samples of different geographical origins in a linear quadrupole ion trap (LQIT) mass spectrometer. CS 2 reagent has been demonstrated previously to generate stable molecular ions for asphaltenes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pinkston et al 36 reported the results from analysis of asphaltenes and asphaltene model compounds by laserinduced acoustic desorption/Fourier transform ion cyclotron resonance mass spectrometry. The authors measured the asphaltenes isolated from a North American crude oil and obtained a MW distribution in the range of 350-1050 Da.…”
mentioning
confidence: 99%
“…Then, the authors concluded that additional studies of alkylated model compounds with bridges are required to define their behavior during the analysis procedures from their instrumentation. 36 Therefore, their analysis results concerning the fundamental properties of asphaltenes are still doubtful.…”
mentioning
confidence: 99%